2020
DOI: 10.1186/s12284-019-0365-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CRISPR-Cas9/Cas12a Ribonucleoprotein Complexes for Genome Editing Efficiency in the Rice Phytoene Desaturase (OsPDS) Gene

Abstract: Background: Delivery of CRISPR reagents into cells as ribonucleoprotein (RNP) complexes enables transient editing, and avoids CRISPR reagent integration in the genomes. Another technical advantage is that RNP delivery can bypass the need of cloning and vector construction steps. In this work we compared efficacies and types of edits for three Cas9 (WT Cas9 nuclease, HiFi Cas9 nuclease, Cas9 D10A nickase) and two Cas12a nucleases (AsCas12a and LbCas12a), using the rice phytoene desaturase (PDS) gene as a target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 31 publications
(33 reference statements)
2
52
0
1
Order By: Relevance
“…CRISPR/Cas editing is regarded as fairly specific in plants assuming stringent target selection (Hahn & Nekrasov, 2019), but efficiency may be increased for certain Cas proteins, depending on the organism to be edited ( Table 1). In rice, off-target edits by both Cas9 and Cas12a appear to rarely occur, but Cas12a may be more efficient for on-target edits (Yin et al, 2017, Tang et al, 2018, Banakar et al, 2020. However, in maize, SpCas9 was more efficient for on-target edits, with no detectable off-target mutations identified in plants from the generation after editing (Lee et al, 2019).…”
Section: Off-target Considerationsmentioning
confidence: 96%
“…CRISPR/Cas editing is regarded as fairly specific in plants assuming stringent target selection (Hahn & Nekrasov, 2019), but efficiency may be increased for certain Cas proteins, depending on the organism to be edited ( Table 1). In rice, off-target edits by both Cas9 and Cas12a appear to rarely occur, but Cas12a may be more efficient for on-target edits (Yin et al, 2017, Tang et al, 2018, Banakar et al, 2020. However, in maize, SpCas9 was more efficient for on-target edits, with no detectable off-target mutations identified in plants from the generation after editing (Lee et al, 2019).…”
Section: Off-target Considerationsmentioning
confidence: 96%
“…Utilizing the LbCas12a nuclease two endogenous rice genes OsPDS and OsBEL were targeted with mutation frequencies of 21.4 and 41.2%, respectively ( Xu et al, 2017 ). An independent study that targeted the disruption of OsPDS by LbCas12a resulted in a similarly high editing frequency of 32.3% ( Banakar et al, 2020 ). Xu et al, 2017 also demonstrated that pre-crRNAs were more efficient in generating mutants than mature crRNAs in rice.…”
Section: Application Of Crispr-cas12a In Agriculturementioning
confidence: 98%
“…Cas12a editing has been widely utilized in many crops (see Table 1 ) including rice ( Endo A. et al, 2016 ; Begemann et al, 2017 ; Hu et al, 2017 ; Tang et al, 2017 , 2018 ; Wang et al, 2017a , b ; Yin et al, 2017 ; Li L. et al, 2018 ; Li et al, 2019a ; Jun et al, 2019 ; Malzahn et al, 2019 ; Banakar et al, 2020 ; Chen et al, 2020 ; Schindele and Puchta, 2020 ), wheat ( Liu et al, 2020 ), maize ( Lee K. et al, 2019 ), soybean ( Kim et al, 2017 ), cotton ( Li B. et al, 2019 ), tomato ( van Vu et al, 2020 ), citrus ( Jia et al, 2019 ), tobacco ( Endo A. et al, 2016 ; Endo and Toki, 2019 ), and the model plant Arabidopsis ( Wolter and Puchta, 2019 ; Schindele and Puchta, 2020 ). At present, three Cas12a genome editing systems AsCas12a, FnCas12a, and LbCas12a have been demonstrated in plants ( Zhong et al, 2018 ) with varied efficiency.…”
Section: Application Of Crispr-cas12a In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…We first applied the double-barrel/CellProfiler™ (DB-CP) system to evaluate the effectiveness of transfection reagent TransIT ® -2020 (Mirus Bio LLC, Madison, WI, USA) for the literature used spermidine as the standard reagent to precipitate DNA onto gold particles [5,23,27] . In recent years, however, TransIT ® -2020 has emerged as an alternative reagent for introducing DNA [28] as well as ribonucleoprotein [29][30][31] into plant tissues. Interestingly, despite its successful application in plants, there has been scant information for optimizing the coating of DNA onto gold with the TransIT ® -2020.…”
Section: Application Of the Double-barrel Cellprofiler™ Systemmentioning
confidence: 99%